Examining the effectiveness of a web-based intervention for symptoms of depression and anxiety in college students: study protocol of a randomised controlled trial. Issue 5 (14th May 2019) - Karyotaki, Eirini; Klein, Anke M; Riper, Heleen; Wit, Leonore de; Krijnen, Lisa; Bol, Eline; Bolinski, Felix; Burger, Simone; Ebert, David D; Auerbach, Randy P; Kessler, Ronald C; Bruffaerts, Ronny; et al.
Abstract : Introduction: The college years are a peak period for the onset of common mental disorders. Poor mental health is associated with low academic attainment, physical, interpersonal and cognitive impairments. Universities can use online approaches to screen students for mental disorders and treat those in need. The present study aims to assess the effectiveness of a guided web-based transdiagnostic individually tailored intervention to treat students with symptoms of depression and/or anxiety. Methods and analysis : The present study is a randomised controlled trial. Participants are Dutch college students (≥18 years) with mild to moderate depression and/or anxiety symptoms. The intervention is a guided web-based transdiagnostic individually tailored intervention that targets symptoms of depression and/or anxiety. The intervention consists of seven online sessions with a duration ranging from 4 to 7 weeks depending on individual progress. A booster session is administered 4 weeks after the completion of the seventh session. Primary outcome measures are the Patient Health Questionnaire for depression and the Generalised Anxiety Disorder 7-item scale for anxiety. These scales are administered at screening, post-treatment and follow-up assessments (6 and 12 months post-randomisation). E thics and dissemination: The Medical Ethics Committee of the Vrije Universiteit Medical Centre has approved the protocol (registration number 2016.583, A2017.362andA2018.421). Results of the trial will be published in a peer-reviewed journal. Trial registration number: NTR6797; Pre-results.